Local taxation, land use regulation, and land use A survey of the evidence - Blöchliger, Hansjörg (OECD Economics Department Working Papers, 2017)
This paper surveys the theoretical and empirical research on the relationship between local taxation, land use regulation and land use patterns. The findings can be summarized as follows: 1) In more fiscally decentralized settings, sub-national land use regulation and fiscal policies encourage urban sprawl. In contrast, in more centralized settings, restrictive urban containment policies and a lack of local fiscal incentives for land development tend to generate housing shortages. 2) Certain fiscal instruments affect the type and composition of land development, e.g. the share of residential versus commercial development. Removing local fiscal incentives for certain property types reduces the amount of land allocated for that type and increases its price. 3) In more decentralized settings, local land use policies aimed at containing or modifying urban growth are ineffective since mobile individuals can circumvent local restrictions by sorting into nearby jurisdictions that offer the preferred combination of land consumption and public services. 4) Expanding transportation networks enables households and firms to move to suburban areas, prompting the central city population to shrink and encouraging sprawl, particularly near major highways. 5) In fiscally decentralized settings, sub-urbanization is associated with a growing political power of homeowners. Homeowners tend to get fiscal zoning policies enacted - mainly via minimum lot size restrictions - that selectively attract well-off local taxpayers. Fiscal zoning thus imposes barriers to local development and raises property values, while at the same time facilitating sprawl. Overall, fiscal policy and land use regulation strongly interact, and governments must align those policies carefully to achieve land-use objectives effectively